What do the CEOs’ LinkedIn posts reveal about their mindsets towards organisational culture? A discourse analysis of LinkedIn posts by the CEOs of Swedish unicorn startups - Ona Žeimytė; Giedrė Lapinskienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Over the past decade, CEOs have increasingly adopted social media as a strategic instrument to engage a broader range of stakeholders, strengthen brand visibility, drive business growth, and convey messages regarding their companies’ organisational culture. In an information-overloaded age, CEOs’ social network communication reflects their attitudes towards organisational culture and sends important signals to both employees and society. The mindsets of unicorn startup leaders attract scientists who seek to identify the key elements of successful business models. This article leverages Edgar Schein’s (1992) organisational culture framework alongside Halliday’s (1961) conception of systemic functional linguistics from the field of discourse analysis studies to identify textual cues that reveal CEOs’ mindsets towards organisational culture. This study aims to systematise the insights into the mindsets of Swedish unicorn CEOs regarding organisational culture, which are collected by analysing their LinkedIn posts. The study has two objectives: a) to identify the key theoretical concepts productive for the analysis of online CEO communication related to organisational culture, and b) to systematise the key elements of organisational culture reflected in the mindsets of CEOs of Swedish unicorn startups expressed in their LinkedIn posts. 72 LinkedIn posts of Swedish unicorn startup CEOs in 2022-2023 have been analysed. The findings show that the mindsets of unicorn CEOs express their inclination towards innovation, growth orientation, visionary thinking, equality, hierarchy, and appreciation as elements of organisational culture. By discussing the process of how CEOs use various textual tools to construct their posts explicitly, the study helps CEOs and their stakeholders gain a better understanding of the effects of these choices and the implicit meanings that are created in this process for improving organisational culture.